2013
DOI: 10.1111/are.12326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein levels on reproductive development and distribution of amino acids in the body tissues of femalePangasianodon hypophthalmus(Sauvage, 1878) broodstock in captivity

Abstract: The present study investigated the optimum dietary protein level for the maturation of adult Pangasianodon hypophthalmus broodstock. Four isocaloric diets containing 250, 300, 350 and 400 g kg À1 of protein levels were prepared and presented to triplicate groups of fish. The fish (mean weight 770 AE 17.23 g and 712 AE 23.42 g for females and males respectively) were stocked in outdoor canvas tanks (4 m 9 1 m 9 1 m) at a stocking density of 20 fish/tank with a male: female ratio of 1:4. The fish were fed the te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 40 publications
4
15
0
Order By: Relevance
“…Therefore, aquaculture nutritionists consistently search for novel, high-quality alternatives of plant and animal origin [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Moreover, [ 16 , 17 , 18 ] it has been reported manipulating the nutrient composition of broodfish diets improves spawning response, lowers the number of broodfish required to achieve production goals, and enhances egg production and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, aquaculture nutritionists consistently search for novel, high-quality alternatives of plant and animal origin [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Moreover, [ 16 , 17 , 18 ] it has been reported manipulating the nutrient composition of broodfish diets improves spawning response, lowers the number of broodfish required to achieve production goals, and enhances egg production and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Deficiency of essential amino acids is known to limit growth, reproductive maturation and protein synthesis (Murai, 1992;Lanes et al, 2012;Kabir et al, 2015). Because the GI increase was significant in the enhanced sea urchins in the current study, deficiency of essential amino acids most likely did not occur.…”
Section: Discussionmentioning
confidence: 74%
“…Besides, Khan et al (2005) stated that the influence of diets with different levels of protein on the composition of fish oocytes has not been totally clarified yet. On the other hand, Kabir et al (2013) suggest that the levels of protein in the muscle, liver and oocytes might be related to weight gain, although the protein content in the oocyte is influenced by the diet, and the nutritional quality of the protein affects the reproductive development and quality of the Pangasianodon hypophthalmus eggs.…”
Section: Discussionmentioning
confidence: 99%
“…According to Kabir et al (2013), the relationship between the content of amino acids in the liver and the oocytes is due to the fact that during oocyte maturation, essential nutrients are transferred from the liver to the oocytes by the blood, and in general, greater protein deposition is observed in the muscles, followed by oocytes and liver. Assem et al (2005) reported that seven amino acids (proline, alanine, valine, methionine, isoleucine, leucine and histi-dine) exhibited significant increase in mature ovaries followed by reduction in spawning for Trachinotus ovatus.…”
Section: Discussionmentioning
confidence: 99%